2008
DOI: 10.1097/mjt.0b013e31815ae755
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With Dexmedetomidine for Monitored Anesthesia Care During ENT Surgical Procedures

Abstract: Dexmedetomidine is an alpha2-adrenergic agonist that produces anxiolysis, amnesia, sedation, potentiation of opioid analgesia, and sympatholysis. It is currently approved by the U.S. Food & Drug Administration for the sedation of adults in the intensive care setting for up to 24 hours during mechanical ventilation. Given its beneficial sedative and anxiolytic properties and limited adverse effect profile, it has been used in several other clinical scenarios. The authors present their experience using dexmedeto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[19] Patients receiving dexmedetomidine can typically respond to commands and perform psychomotor tests when lightly aroused from their sedate state without a need to decrease or stop the dexmedetomidine infusion. [10] In our study, we found that the dexmedetomidine-treated patients were sedated; they appeared to be asleep but were easily aroused with verbal or physical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Patients receiving dexmedetomidine can typically respond to commands and perform psychomotor tests when lightly aroused from their sedate state without a need to decrease or stop the dexmedetomidine infusion. [10] In our study, we found that the dexmedetomidine-treated patients were sedated; they appeared to be asleep but were easily aroused with verbal or physical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The BIS, VAS scores, modified OAA/S scores of sedation, vital signs, respiratory rates and end-tidal carbon dioxide levels were also measured simultaneously. 15,16 …”
Section: Study Assessmentmentioning
confidence: 99%
“…Monitored anesthesia care has been widely used in many clinical fields such as gastrointestinal endoscopy, septoplasty, thyroplasty, interventional or radiological procedures, cataract surgery, and awake bronchoscopy intubation (Bekker and Sturaitis, 2005; Busick et al, 2008; Goksu et al, 2008; Dogan et al, 2010; Parikh et al, 2013; Mondal et al, 2015). It can provide suitable intraoperative conditions for both patients and surgeons alike while avoiding the adverse reactions of GA, e.g., hemodynamic instability and prolonged emergence.…”
Section: Discussionmentioning
confidence: 99%